Pendekatan Socioecological Model untuk Meningkatkan Kompetensi Kader Posbindu dalam Pengelolaan Program Prolanis di Wilayah Kerja Puskesmas Padasuka Kota Bandung Jawa Barat - Sri Sumartini; Septian Andriyani; Linda Amalia; Tirta Adikusuma Suparto; Asih Purwandari Wahyoe Puspita (Universitas Mathla'ul Anwar Banten, 2020)
SOCIOECOLOGICAL MODEL APPROACH TO IMPROVE POSBINDU CADRE COMPETENCE IN PROLANIS PROGRAM MANAGEMENT IN THE WORK AREA OF PUSKESMAS PADASUKA, BANDUNG CITY, WEST JAVA. Socioecological models include promotive and preventive efforts, the government launched PROLANIS as an effort carried out by BPJS Health in the JKN era. The number of elderly people is always increasing and it is known that about 12% of the population in Indonesia is elderly, becoming one of the factors increasing the number of chronic degenerative diseases such as type II diabetes mellitus and hypertension. Coverage of health services for the elderly is still very low at 30.72%. Public awareness needs to be increased to control risk factors that might arise, through the chronic health care program that often occurs in the elderly should be prevented by promotive and preventive efforts. Posbindu Cadre Empowerment through increased competence with the socio ecological model approach, namely prevention programs and promoting the resolution of health problems can be done together. The purpose of the program is to develop and implement a program to develop Posbindu cadres in the Prolanis program. In carrying out this activity, Posbindu cadres. The program began with the identification of problems with prolanis, posbindu cadre health programs, health promotion, cadre training, and posbindu grouping. The method used is descriptive quantitative. The results obtained that there is an increase in the competence of cadres in the postbindu knowledge about PROLANIS.